Effect of Selected Parameters on Field Performance of a Tractor-operated Sugarcane Cleaner - Khar, Sanjay; Shukla, L N (Journal of Agricultural Engineering, 2006)
The performance of a tractor-operated cleaner was evaluated with two varieties of sugarcane viz. COJ-64 and CO-1148. The effect of flap roller speed and number of canes fed at a time on the detopping efficiency, mill trash, stripping efficiency, cane loss, cane damage and cane output were studied. The detopping and stripping efficiency increased with the increase in the flap roller speed whereas it decreased with the increase in the number of canes fed at a time. Higher detopping, stripping efficiency and lower mill trash percentage was obtained in case of CO-1148 variety as compared to COJ-64 variety for all the treatments under study.